Development of Learning Outcome Assessment Instruments with Mathematics Communication Ability in High School Mathematics Learning - Dewi Nasiroh (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2021)
This study (1) develop a learning assessment instrument with the assignment technique-oriented to mathematical communication ability in high school mathematics of trigonometry material (2) reveal the feasibility of the developed instrument, (3) reveal the characteristics of the developed instrument, (4) reveal the users' responses to the instrument, (5) measure the ability of mathematical communication of the students on high school mathematics in learning trigonometry. This study was research and development using the procedure of tests preparation based on Mardapi (2017 ) with the steps including preparing test specifications, writing test questions, reviewing tests, administering tests, analyzing tests items, improving the tests, assembling the tests, administering the tests and interpreting results. The initial product was field-tested to 254 students of high schools in Yogyakarta City. The result of the research was an assessment instrument of learning outcomes with assignment technique-oriented to the mathematical communication ability in high school mathematics learning of trigonometry. The Aiken index was 0.7 for this instrument, and the instrument was reliably tested to a test of participants with the ability ( q ) between -4.07 logits < q <3.79 logits. The teachers' responses to test instruments were good. The results of field trials showed that 20 items fit with the PCM model. The level of difficulty was in the range of -1.29 logits <b < 1.32 logits. The function of the test information Obtained by q = -0.11 logit and the standard error of measurement was 0:18. The measurement result of 90 students shows that the student's mathematical communication ability was 67%.